Experiences of Women in Tianguis and Popular Markets in Oaxaca - Nallely Guadalupe Tello Méndez (Íconos)
This article reflects on two experiences of participation in tianguis and markets of women whose lives were transformed by the Popular Oaxaca Movement of 2006. The first experience is of the New Woman Collective, dating back to the assemblage of a group of women that met for the first time and developed an affinity. In the heat of the struggle, these women decided to take a risk and construct a popular tianguis that would foster discussions, analyses of buying and selling products, and that tried to foster the creation of alternatives to the current political and economic system. The second case alludes to an individual experience of a female worker who lost her remunerated job due to the economic crisis generated in 2006 in Mexico, opting to work selling tortillas as a family business and form of sustenance.